Structure of the Bacillus anthracis dTDP‐l‐rhamnose‐biosynthetic enzyme dTDP‐4‐dehydrorhamnose 3, 5‐epimerase (RfbC). Issue 12 (4th December 2017) - Shornikov, Aleksander; Tran, Ha; Macias, Jennifer; Halavaty, Andrei S.; Minasov, George; Anderson, Wayne F.; Kuhn, Misty L.
Abstract : The crystal structure of dTDP‐6‐deoxy‐d ‐ xylo ‐4‐hexulose 3, 5‐epimerase (RfbC) from B. anthracis was determined at 1.63 Å resolution in complex with dTDP and pyrophosphate. RfbC is the third enzyme of the dTDP‐l ‐rhamnose‐biosynthetic pathway and only crystallized in the presence of the other three members of the pathway RfbA, RfbB and RfbD. Abstract : The exosporium layer of Bacillus anthracis spores is rich inl ‐rhamnose, a common bacterial cell‐wall component, which often contributes to the virulence of pathogens by increasing their adherence and immune evasion. The biosynthetic pathway used to form the activatedl ‐rhamnose donor dTDP‐l ‐rhamnose consists of four enzymes (RfbA, RfbB, RfbC and RfbD) and is an attractive drug target because there are no homologs in mammals. It was found that co‐purifying and screening RfbC (dTDP‐6‐deoxy‐d ‐ xylo ‐4‐hexulose 3, 5‐epimerase) from B. anthracis in the presence of the other three B. anthracis enzymes of the biosynthetic pathway yielded crystals that were suitable for data collection. RfbC crystallized as a dimer and its structure was determined at 1.63 Å resolution. Two different ligands were bound in the protein structure: pyrophosphate in the active site of one monomer and dTDP in the other monomer. A structural comparison with RfbC homologs showed that the key active‐site residues are conserved across kingdoms.